2019
DOI: 10.1002/pits.22325
|View full text |Cite
|
Sign up to set email alerts
|

Independent evaluation of Q‐Interactive: A paper equivalency comparison using the PPVT‐4 with preschoolers

Abstract: Pearson now uses a technology‐based testing platform, Q‐Interactive, to administer tests previously available in paper versions. The same norms are used for both versions; Pearson's in‐house equivalency studies indicated that both versions are equated. The goal of the current study is to independently evaluate equivalency findings. For the current study, equivalency was measured using the three‐part test set forth by American Psychological Association in 1986. First, the researchers examined rank order similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Everything is included in one location, a tablet, rather than multiple materials (e.g., protocol, administration manual, notepad, or stopwatch). Krach et al ( 2019 ) reported that a set of tablets containing two complete tests may weigh 5 lbs, where the equivalent paper version with all of its materials might weigh 20 lbs or more. This is no small consideration for individuals who must daily transport test materials into and out of school buildings.…”
Section: Q-interactivementioning
confidence: 99%
“…Everything is included in one location, a tablet, rather than multiple materials (e.g., protocol, administration manual, notepad, or stopwatch). Krach et al ( 2019 ) reported that a set of tablets containing two complete tests may weigh 5 lbs, where the equivalent paper version with all of its materials might weigh 20 lbs or more. This is no small consideration for individuals who must daily transport test materials into and out of school buildings.…”
Section: Q-interactivementioning
confidence: 99%
“…Adaptation equivalency guidelines were set forward by the American Psychological Association (APA, 1986) in the Guidelines for Computer-Based Tests and Interpretations as well as by a joint commission in the Standards for Educational and Psychological Testing (AERA et al, 2014). Additional equivalency requirements were set forward by Grosch et al (2011), Hodge et al (2019), Krach, McCreery et al (2020), Cohen (1988), andFarmer et al (2020). Table 2 lists these guidelines as well as the parameters for how to evaluate each one when reading an equivalency study.…”
Section: Using the Potential Guidementioning
confidence: 99%
“…Use of any adapted, tele-assessment instrument lacking concurrent validity data between face-to-face and tele-assessment versions is not recommended. To feel truly comfortable with version equivalency, all of these standards should be met:research should be published in a reputable, academic source;between version correlations should be at or above .80 (Krach, McCreery et al, 2020). Concurrent validity standards are not sufficient for equivalency studies;no statistically significant differences between scores derived via different formats (AERA, APA, & NCME, 2014; APA, 1986);between version effect sizes should be at or below .2 (Daniel, Wahstrom, & Zang, 2014);normative dispersion of scores should have a statistically similar shape (AERA et al, 2014; APA, 1986);samples used in the study should match the U.S.…”
Section: Using the Potential Guidementioning
confidence: 99%
See 2 more Smart Citations